Differential Virulence Among Geosmithia morbida Isolates Collected Across the United States Occurrence Range of Thousand Cankers Disease - Chahal, Karandeep; Gazis, Romina; Klingeman, William; Lambdin, Paris; Grant, Jerome; Windham, Mark; Hadziabdic, Denita (Frontiers in Forests and Global Change, 2022)
Thousand Cankers Disease (TCD), first documented in the western U.S. in the early 2000s, has spread into nine western and seven eastern U.S. states, and northern Italy. TCD incidence and severity differ between eastern and western U.S. outbreak localities. Black walnut (Juglans nigra) trees, introduced into both urban and plantation settings in the western U.S., have been severely impacted as evident by the documented high disease incidence and mortality. However, in eastern U.S. localities, where J. nigra is native, host-pathogen-vector interactions resulted in two different outcomes: trees either die or partly recover following infection. Recent genetic studies on the TCD causal agent, Geosmithia morbida, indicate spatial genetic structure and high levels of genetic diversity among U.S. populations. Using detached branch inoculation assays, we report differential virulence among 25 G. morbida isolates collected across the current distribution range of the disease. As a proxy for virulence, canker area was measured seven days after inoculation. Varying degrees of virulence were observed among tested G. morbida isolates which was partly explained by their genetic provenance (genetic clusters). Isolates that grouped within genetic cluster 2 (n=7 from eastern U.S., and n=6 from western U.S.; mean=210.34 mm2) induced significantly larger cankers than isolates that grouped within genetic cluster 1 (n=12; all western U.S. isolates; mean=153.76 mm2). Canker sizes varied among isolates within each genetic cluster and were not correlated with geographic region (eastern vs. western U.S.), but rather to the isolate state of origin. Mean canker size also differed in response to isolates that originated from different tree host species. Geosmithia morbida isolates collected from J. major induced statistically smaller cankers when compared to isolates recovered from undetermined Juglans species but not from J. nigra. In sum, the increased mortality reported for western U.S. walnut tree populations can’t be explained by a higher virulence of local G. morbida. Plausible explanations for the observed disparity include environmental conditions such as prolonged drought, greater population densities of walnut twig beetle causing higher number of inoculation events to individual trees, and multiple introductions of G. morbida originating from multiple locations.